Intestinal absorption of calcium in greyhounds: the response to intermittent and continuous administration of human synthetic parathyroid hormone fragment 1-34 (hPTH 1-34). - Podbesek, R; Mawer, E; Zanelli, G; Parsons, J; Reeve, J (1984)
Long-term studies of gastrointestinal radio-calcium absorption were undertaken in adult greyhounds before and during two treatment regimes with human parathyroid hormone fragment 1-34 (hPTH 1-34). The results were correlated with plasma vitamin D metabolite levels and kinetic indices related to the balance of fluxes of calcium between plasma and the rapidly exchangeable calcium pools of bone. Compared with adult man, results obtained before treatment started showed lower indices of gastrointestinal calcium absorption and considerably higher concentrations of 24-hydroxycalcidiol in the dogs. Daily injections of hPTH 1-34 at 1.7 microgram day-1 kg-1 significantly increased indices of radiocalcium absorption and plasma calcitriol concentrations, while only causing transient calcaemic responses. The individual magnitudes of the calcaemic response correlated positively with indices of radiocalcium retention in the exchangeable pools of bone which in turn correlated positively with 'late-phase' absorption of radiocalcium from the gut. Subcutaneous infusions of hPTH 1-34 at 0.5 microgram day-1 kg-1 to the same dogs were just insufficient to cause hypercalcaemia, but increased plasma calcitriol concentrations. Indices of radiocalcium absorption were not increased. Continuous parathyroid hormone (PTH) infusion is now known to substantially down-regulate renal PTH receptor density, whereas recovery after a brief exposure to PTH occurs within 24 h. It is possible that the differences in response of the gut to the two regimes may in part be related to their differing effects on some PTH receptors.